DEVELOPMENT OF 23 CYCLES ACTIVITY IN NORTHERN AND SOUTHERN HEMISPHERES OF THE SUN - Ryabov, M. I.; Sukharev, A. L.; Lukashuk, S. A. (Одеські астрономічні публікації, 2013)
On an example of the 23rd cycle of solar activity the basic properties of its development in northern and southern hemispheres were researched (daily values of Wolf Sunspot Number - W, the daily values of Sun spots areas - Sp and daily values of flare index - FI.) Effects of application of full-scale Wavelet analysis for studying the temporary structure of formation of a solar cycle show the difference in northern and southern hemispheres. The "leading" periods (in northern hemisphere - 340 days, and in southern hemisphere - 709 days) differ. Thus, the activity period in two years is predominate in southern hemisphere. The "leading" period for the flare index for northern hemisphere is 555 days, and for southern hemisphere is 709 days. In general the basic periods W in northern hemisphere are in the range of 37-555 days, and in southern - 78-906 days, SpN (61-906 days), SpS (61-1477 days), FIN (37-555 days), FIS (23-709 days), FIS - (14709 days) depending on the phase of solar cycle.